Voltammetric Quantification of Paraquat and Glyphosate in Surface Waters - Alza-Camacho, William Roberto; García-Colmenares, José Mauricio; Chaparro-Acuña, Sandra Patricia (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
The indiscriminate use of pesticides on crops has a negative environmental impact that affects organisms, soil and water resources, essential for life. Therefore, it is necessary to evaluate the residual effect of these substances in water sources. A simple, affordable and accessible electrochemical method for Paraquat and Glyphosate quantification in water was developed. The study was conducted using as supporting electrolyte Britton-Robinson buffer solution, working electrode of glassy carbon, Ag/AgCl as the reference electrode, and platinum as auxiliary electrode. Differential pulse voltammetry (VDP) method for both compounds were validated. Linearity of the methods presented a correlation coefficient of 0.9949 and 0.9919 and the limits of detection and quantification were 130 and 190 mg/L for Paraquat and 40 and 50 mg/L for glyphosate. Comparison with the reference method showed that the electrochemical method provides superior results in quantification of analytes. Of the samples tested, a value of Paraquat was between 0,011 to 1,572 mg/L and for glyphosate it was between 0.201 to 2.777 mg/L, indicating that these compounds are present in water sources and that those may be causing serious problems to human health.